2006
DOI: 10.1111/j.1469-0691.2006.01475.x
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 1 and respiratory disease in critically-ill patients: real pathogen or innocent bystander?

Abstract: Herpes simplex virus type 1 (HSV-1) has been associated with pulmonary disease, mostly in severely immunocompromised patients. After reactivation and shedding in the oropharynx, the virus may reach the lower respiratory tract by aspiration or by contiguous spread. HSV-1 can be detected in clinical specimens by virus culture or quantitatively by nucleic acid amplification techniques. With these techniques, HSV-1 is often detected in the respiratory secretions of critically-ill patients. However, a clear diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
118
2
15

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(136 citation statements)
references
References 87 publications
1
118
2
15
Order By: Relevance
“…Blood samples to determine the HSV IgG status of patients on admission to ITU were not available. No overt case of HSV pneumonia was diagnosed in any patient in whom HSV was detected although the diagnosis of this condition is easily missed [Simoons-Smit et al, 2006]. This has been noted in studies in which HSV has been detected in tracheal or bronchial secretions without there being evidence of classical HSV pneumonia such as HSV inclusions demonstrated histologically [Verheij et al, 2004;Daubin et al, 2005].…”
Section: Discussionmentioning
confidence: 92%
“…Blood samples to determine the HSV IgG status of patients on admission to ITU were not available. No overt case of HSV pneumonia was diagnosed in any patient in whom HSV was detected although the diagnosis of this condition is easily missed [Simoons-Smit et al, 2006]. This has been noted in studies in which HSV has been detected in tracheal or bronchial secretions without there being evidence of classical HSV pneumonia such as HSV inclusions demonstrated histologically [Verheij et al, 2004;Daubin et al, 2005].…”
Section: Discussionmentioning
confidence: 92%
“…The clinical significance of detecting evidence of HSV in patients presenting with pneumonia remains controversial. 9 It is likely that in most patients it represents evidence of reactivation of latent HSV infection rather than evidence of a true viral pneumonitis. Studies in ventilated patients with pneumonia have shown a high incidence of PCR-detectable HSV in respiratory samples and it is unclear whether there is any specific benefit in initiating treatment in the absence of other features to suggest a true viral pneumonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Primer enfeksiyondan sonra virüsün latent enfeksiyonları tükürükle asemptomatik atılım, ağız içi mukozal ülserler veya oro-labial lezyonlar gibi basit reaktivasyonlarla karşımıza çıka-bildiği gibi, immünyetmezliği olan hastalarda herpetik özofa-jit, trakeo-bronşit ve pnömoni gibi ciddi hastalıklara yol aça-bilir. Primer enfeksiyon genellikle asemptomatik olduğu için reaktivasyon HSV enfeksiyonunun ilk görülme şekli olabilir 4,5 .…”
Section: Introductionunclassified
“…Bu yolla yayılım diffüz interstisyel pnömoniye yol açar. Üçüncü yol ise vagal gangliondaki latent infeksiyonun reaktivasyonu ile nervus vagus aracılığı ile akciğer epiteline yayılımdır (4). Orta ve alt solunum yolunun HSV enfeksiyonları nadir görülür ve genellikle immünyetmezliği olan hastalardır.…”
Section: Introductionunclassified
See 1 more Smart Citation